Relationship between chlorophyll-a and sea surface temperature to tuna catch in the Southern Water of Java - Ahmad Faizal Abidin; amron amron; Marza Ihsan Marzuki (Faculty of Mathtmatics and Natural Sciences, 2020)
The Southern Waters of Java included in 573 WPP has high fishing activity, which the most important commodity is Tuna. The number of Tuna catch are fluctuated which influenced by oceanography factors in the waters. Some of the factors that affect the catch are sea surface temperature (SST) and chlorophyll-a, so this study aimed to determine the distribution, fluctuations in SST and chlorophyll-a, and its relationship to the Tuna catch. SST and chlorophyll-a data were downloaded from NASA, and Tuna catch data in 2017 was collected from Cilacap Fishing Port. The relationship between SST and chlorophyll-a with the catch was analyzed with cross correlation analysis. Distribution of SST and chlorophyll-a was higher in the east part and coastal areas compared to the western and offshore parts. SST and chlorophyll-a fluctuations are inversely proportional but have a very close relationship. SST in the western season and transition 1 an increase then a decline in the east season and transition II, while chlorophyll-a in the western season and transition I is lower than in the east season and transition II. The highest correlation between SST and catch in the time lag -3, while chlorophyll-a in the lag time -4.